2006
DOI: 10.1016/j.envres.2005.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Menarche in women with high exposure to persistent organochlorine pollutants in utero and during childhood

Abstract: In animal studies, exposure to persistent organochlorine pollutants (POPs) in utero and through mother's milk has been suggested to affect the onset of puberty. However, human studies are scarce and ambiguous. In the present study, information on age at menarche was collected from 545 women who had been brought up in a fishing village/family at the Swedish east coast, off the Baltic Sea, and therefore were assumed to have been exposed to POPs in utero, through breast feeding, and/or through dietary habits duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
(42 reference statements)
0
14
0
2
Order By: Relevance
“…The studies of Axmon (2006) and Denham et al (2005) indicated that exposure to organochlorine pollutants and toxic elements have negative effects on age at menarche. Aschengrau et al (1989) reported higher spontaneous abortions among women exposed to As through drinking water.…”
Section: Resultsmentioning
confidence: 99%
“…The studies of Axmon (2006) and Denham et al (2005) indicated that exposure to organochlorine pollutants and toxic elements have negative effects on age at menarche. Aschengrau et al (1989) reported higher spontaneous abortions among women exposed to As through drinking water.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to tetrachlorodibenzo-p-dioxin (TCDD) (7) was associated with delayed breast development, and slight delays in age at menarche were observed among consumers of contaminated Baltic Sea fish (8). However, age at menarche was not related to dioxin exposure in the den Hond study (7), and no effect on menarchal age was observed among girls exposed to dioxin prepuberty in Seveso (9).…”
Section: Pubertymentioning
confidence: 90%
“…Only a few studies have examined exposures at the time of organogenesis, even though fetal programming of the timing of menarche is likely (Vatten et al, 2003;Windham et al, 2004;Axmon, 2006). The increasing trend of delayed childbearing may be one factor affecting prenatal programming.…”
Section: Introductionmentioning
confidence: 99%